Efektifitas Model Pembelajaran Tgt Pada Materi Vektor Terhadap Hasil Belajar Kognitif Siswa SMAN 10 Semarang - Maryam Nabila Bilqist; Agnita Siska Pramasdyahsari; Elfa Mawadati; Dina Prasetyawati (Journal on Education, 2024)
This study aims to determine the effectiveness of Teams Games Tournament (TGT) learning in improving cognitive learning outcomes to grade XI students on vector materials. The design of this study was a pretest- posttest control group design. The sample in this study involved 63 students from grades XI-1 and XI-2 of SMAN 10 Semarang, who were randomly selected using random sampling techniques. Based on the results of the analysis using the independent T-test with the help of SPSS in this study, it was found that the calculated T-value produced was less than the 5% significance level, namely 0.030 <0.05. This finding indicates a significant difference in the average between the experimental group and the control group. From these results it can be concluded that the use of the TGT learning model is more effective than the conventional approach using the lecture method.